Social media for creative libraries - Bradley, Phil, 1959- (London : Facet Publishing, 2015)
The fully revised and updated second edition of this book from acclaimed author Phil Bradley takes a clear and practical approach as it explains exactly how to use the different types of Web 2.0 technologies, and shows how libraries can get the most out of them (using case studies). Illustrations help guide readers through each step of creating a range of resources, and a companion website, including podcasts from the author, ensures readers are kept up to date in this highly dynamic and fast-moving area. Several new chapters look at the following key areas: social networking; presentations; social search engines; twitter; and, new trends and Web 3.0. This is essential reading for library and information professionals wishing to harness the social networking revolution to their advantage. It will also be valuable for website authors and students of library and information studies.
An introduction to social media -- Authority checking -- Guiding tools -- Current awareness and selective dissemination of information resources -- Presentation tools -- Teaching and training -- Communication -- Marketing and promotion : the groundwork -- Marketing and promotion : the practicalities -- Creating a social media policy.
Includes index.
Keywords: World Wide Web; Internet; Libraries